The Use of Picture Series to Improve Eighth Graders’ Writing Recount Texts - Muhammad Lukman Syafii (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2016)
This study involved eighth graders’ of MTs Al-Islam Nganjuk and focused on their ability in writing recount text. Based on the result of preliminary study, it was found that the students’ writing ability got unsatisfactory results. Therefore, this classroom action research was conducted. The finding of the study indicated that the implementation of picture series was successful. It showed that the students gained good progress from the first to the second cycle. The data analysis confirmed 71.90%, (in cycle I), 79.50% (in cycle II) students were actively involved. Hence, this study is effective to improve the students’ writing